Variations in infection control practices suggest a need for guidelines in primary ciliary dyskinesia patient care. Issue 4 (28th January 2022) - Caliskan, Ayse B.; Horani, Amjad; Manion, Michele; Brody, Steven L.
Abstract: Primary ciliary dyskinesis (PCD) is an autosomal recessive disorder associated with impaired mucociliary clearance caused by defects in ciliary structure and function. The major clinical feature of PCD is recurring or persistent respiratory tract infection. Respiratory tract colonization with drug‐resistant organisms impacts the frequency of infections and lung function decline. Protective gear has been employed by caregivers in an attempt to control respiratory tract bacterial spread between patients with cystic fibrosis, but use in PCD is not known. We conducted a web‐based survey to investigate infection control and prevention practices of PCD centers in North America, and how practices have been influenced by the COVID‐19 pandemic. The response rate was 87.0%. Before the COVID‐19 pandemic, glove, gown, and mask use were variable, and only 3.7% of centers used masks during encounters with PCD outpatients. After COVID‐19 mandates are lifted, 48.1% of centers plan to continue to use masks during outpatient care, while the practice regarding the use of gloves and gowns was not influenced by the current pandemic. There is no uniform practice for infection control in PCD care indicating the need for practice guidelines. Mitigation of respiratory virus transmission learned during the COVID‐19 pandemic may impact future infection control approaches used for patients with PCD and other lung diseases.